Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1) \(\frac{25}{12}.x+\frac{11}{15}=\frac{9}{10}\)
=> \(\frac{25}{12}.x=\frac{9}{10}-\frac{11}{15}\)
=> \(\frac{25}{12}.x=\frac{1}{6}\)
=> \(x=\frac{1}{6}:\frac{25}{12}\)
=> \(x=\frac{2}{25}\)
Vậy \(x=\frac{2}{25}\).
3) \(\frac{29}{12}.\left[x\right]-\frac{5}{6}=\frac{3}{8}\)
=> \(\frac{29}{12}.\left[x\right]=\frac{3}{8}+\frac{5}{6}\)
=> \(\frac{29}{12}.x=\frac{29}{24}\)
=> \(x=\frac{29}{24}:\frac{29}{12}\)
=> \(x=\frac{1}{2}\)
Vậy \(x=\frac{1}{2}\).
4) \(\left[4x+\frac{3}{4}\right]-\frac{5}{4}=2\)
=> \(\left[4x+\frac{3}{4}\right]=2+\frac{5}{4}\)
=> \(4x+\frac{3}{4}=\frac{13}{4}\)
=> \(4x=\frac{13}{4}-\frac{3}{4}\)
=> \(4x=\frac{5}{2}\)
=> \(x=\frac{5}{2}:4\)
=> \(x=\frac{5}{8}\)
Vậy \(x=\frac{5}{8}\).
5) 2x + 2x+3 = 144
⇔ 2x + 2x . 23 = 144
⇔ 2x . (1 + 23) = 144
⇔ 2x . 9 = 144
⇔ 2x = 144 : 9
⇔ 2x = 16
⇔ 2x = 24
=> x = 4
Vậy x = 4.
Chúc bạn học tốt!
=> [2x -1/5]^2 = 4/25 => 2x -1/5 = -2/5 hoặc 2/5
=> 2x = -1/5 hoặc 3/5 => x= -1/10 hoặc x= 3/10
1: Ta có: \(2x+x\left(x-5\right)=3x^2-x\)
\(\Leftrightarrow2x+x^2-5x-3x^2+x=0\)
\(\Leftrightarrow-2x^2-2x=0\)
\(\Leftrightarrow-2x\left(x+1\right)=0\)
Vì -2≠0
nên \(\left[{}\begin{matrix}x=0\\x+1=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=0\\x=-1\end{matrix}\right.\)
Vậy: x∈{0;-1}
2) Ta có: \(15-5\left(1-2x\right)=12-x\)
\(\Leftrightarrow15-5+10x-12+x=0\)
\(\Leftrightarrow11x-2=0\)
\(\Leftrightarrow11x=2\)
hay \(x=\frac{2}{11}\)
Vậy: \(x=\frac{2}{11}\)
3) Ta có: \(\frac{2}{3}-\frac{1}{3}\left(x-\frac{3}{2}\right)-\frac{1}{2}\left(2x+1\right)=5\)
\(\Leftrightarrow\frac{2}{3}-\frac{1}{3}x+\frac{1}{2}-x-\frac{1}{2}-5=0\)
\(\Leftrightarrow\frac{-13}{3}-\frac{4}{3}x=0\)
\(\Leftrightarrow\frac{4}{3}x=\frac{-13}{3}\)
hay \(x=\frac{-13}{3}:\frac{4}{3}=\frac{-13}{4}\)
Vậy: \(x=\frac{-13}{4}\)
4) Ta có: \(\left|x-\frac{4}{5}\right|=\frac{3}{5}\)
\(\Leftrightarrow\left[{}\begin{matrix}x-\frac{4}{5}=\frac{3}{5}\\x-\frac{4}{5}=\frac{-3}{5}\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=\frac{7}{5}\\x=\frac{1}{5}\end{matrix}\right.\)
Vậy: \(x\in\left\{\frac{1}{5};\frac{7}{5}\right\}\)
1. \(2x+x\left(x-5\right)=3x^2-x\)
\(\Leftrightarrow2x+x^2-5x=3x^2-x\)
\(\Leftrightarrow\left(2x-5x+x\right)+\left(x^2-3x^2\right)=0\)
\(\Leftrightarrow-2x-2x^2=0\)
\(\Leftrightarrow-2x\left(1+x\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}-2x=0\\1+x=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=0\\x=-1\end{matrix}\right.\)
2. \(15-5\left(1-2x\right)=12-x\)
\(\Leftrightarrow15-5+10x=12-x\)
\(\Leftrightarrow\left(15-5-12\right)+\left(10x+x\right)=0\)
\(\Leftrightarrow-2+11x=0\)
\(\Leftrightarrow11x=2\Leftrightarrow x=\frac{2}{11}\)
3. \(\frac{2}{3}-\frac{1}{3}\left(x-\frac{3}{2}\right)-\frac{1}{2}\left(2x+1\right)=5\)
\(\Leftrightarrow\frac{2}{3}-\frac{1}{3}x+\frac{1}{2}-x-\frac{1}{2}=5\)
\(\Leftrightarrow\left(\frac{2}{3}+\frac{1}{2}-\frac{1}{2}-5\right)-\left(\frac{1}{3}x+x\right)=0\)
\(\Leftrightarrow-\frac{13}{3}-\frac{4}{3}x=0\)
\(\Leftrightarrow-\frac{4}{3}x=\frac{13}{3}\Leftrightarrow x=-\frac{13}{4}\)
4. \(\left|x-\frac{4}{5}\right|=\frac{3}{5}\)
\(\Rightarrow x-\frac{4}{5}=-\frac{3}{5}\) hoặc \(x-\frac{4}{5}=\frac{3}{5}\)
\(TH1:x-\frac{4}{5}=-\frac{3}{5}\Rightarrow x=\frac{1}{5}\)
\(TH2:x-\frac{4}{5}=\frac{3}{5}\Rightarrow x=\frac{7}{5}\)